2017
DOI: 10.1016/j.ijmm.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Limitations in the use of PSMγ, agr , RNAIII, and biofilm formation as biomarkers to define invasive Staphylococcus epidermidis from chronic biomedical device-associated infections

Abstract: Staphylococcus epidermidis is a common cause of biomedical device-associated infections. Agr is the major quorum sensing system in staphylococci and regulates virulence factors. Four agr-specificity groups exist in S. epidermidis, and chronic S. epidermidis infections are hypothesised to select for agr-negative phenotypes. Therefore, we investigated S. epidermidis strains from prosthetic joint- and catheter-associated infections to establish i) whether an infection selects for an agr-negative phenotype; ii) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In addition, Jarraud et al (2000) have shown that S. aureus endocarditis strains were mainly associated with phylogenetic group AF2 ( agr groups I or II) while phylogenetic group AF1 ( agr group IV) strains are mainly responsible for generalized exfoliative syndromes and bullous impetigo. Similarly, agr -specificity groups in S. epidermidis are also associated with specific clinical infections (Hellmark et al, 2013; Harris et al, 2017). The potential impact of this CC- agrSl- type association on the regulation of virulence could be explored by a functional analysis of the agr locus in S. lugdunensis .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Jarraud et al (2000) have shown that S. aureus endocarditis strains were mainly associated with phylogenetic group AF2 ( agr groups I or II) while phylogenetic group AF1 ( agr group IV) strains are mainly responsible for generalized exfoliative syndromes and bullous impetigo. Similarly, agr -specificity groups in S. epidermidis are also associated with specific clinical infections (Hellmark et al, 2013; Harris et al, 2017). The potential impact of this CC- agrSl- type association on the regulation of virulence could be explored by a functional analysis of the agr locus in S. lugdunensis .…”
Section: Discussionmentioning
confidence: 99%
“…The agr system plays a critical role in the biofilm life cycle and virulence of S. epidermidis , making chemical or biological agents capable of agr modulation valuable tools to probe and potentially limit infectivity. ,,,, The intentional activation of agr could reduce biofilm accumulation and thereby render the dispersed bacteria more susceptible to antimicrobial agents . In this study, we report the design, synthesis, and biological characterization of AIP signal analogues capable of agonizing three specificity groups of S. epidermidis (I–III).…”
Section: Summary and Conclusionmentioning
confidence: 99%
“…Pathogenesis in S. epidermidis is largely under the regulation of quorum sensing (QS), a chemical-based cell–cell communication system, which makes QS an attractive target to potentially attenuate virulence phenotypes in this bacterium. QS activation can increase S. epidermidis ’ capability for skin colonization, evasion of the host immune system, and tissue infiltration. , In contrast, QS inhibition in S. epidermidis has been shown to allow for more resilient biofilm formation, shielding S. epidermidis from antibiotics and the immune system. ,, Non-native small molecules and peptides capable of either inhibiting or activating QS have been developed in other bacteria and have shown significant value as research tools and as potential antivirulence agents. While there are merits to either intentionally activating or inhibiting QS to curb S. epidermidis infections, given that the primary mechanism by which S. epidermidis causes device-associated infections is through biofilm formation, ,, this connection suggests that the development of chemical tools to agonize QS and thereby promote biofilm dispersion may provide the most benefit in reducing S. epidermidis growth on surfaces and rendering them more vulnerable to treatment with antibiotics or clearance via the host immune system. , Studies in S. aureus , which utilizes a similar QS system to regulate biofilm formation, have demonstrated that activation of QS through addition of agonists dispersed biofilms, significantly increasing their susceptibility to antibiotics relative to untreated S. aureus biofilms . Identifying such QS agonists to combat S. epidermidis biofilms was a motivation for the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus epidermidis is a ubiquitous, skin-colonizing Gram-positive bacterium that has emerged as an opportunistic pathogen in many hospital-acquired infections. , This bacterium is now a leading cause of biomedical device-associated infections due to its propensity to form robust biofilms on abiotic surfaces. This biofilm lifestyle, combined with its increasing antibiotic resistance, makes treating S. epidermidis infections with traditional antibacterial drugs difficult. ,,, Playing an important role in the pathogenesis of S. epidermidis infections is the accessory gene regulator ( agr ) system, a cell–cell communication system that allows the bacteria to sense population density and coordinate gene expression at high cell numbers to initiate group behaviors. , This cell–cell signaling process is a type of quorum sensing (QS, Figure ) and is mediated in S. epidermidis by a macrocyclic peptide pheromone called an autoinducing peptide (AIP). As the bacterial population density increases, so does the concentration of the AIP. Once a threshold concentration is reached, the AIP can productively bind with its cognate receptor AgrC, a transmembrane histidine kinase, which subsequently initiates the signaling cascade that leads to changes in gene expression …”
Section: Introductionmentioning
confidence: 99%